Assessing structure/property relationships and synthetic protocols in the fabrication of poly(oxanorbornene imide) single-chain nanoparticles. (March 2019) - Chen, Ruiwen; Benware, Sarah J.; Cawthern, Sawyer D.; Cole, Justin P.; Lessard, Jacob J.; Crawford-Eng, Isabelle M.; Saxena, Riya; Berda, Erik B.
Graphical abstract: Highlights: Synthesis of poly(oxanorbornene imide)s via ring-opening metathesis polymerization (ROMP). Special processing conditions to prevent undesired premature reaction. SCNP formation by intra-chain radical polymerization of pendant methacryloyl groups. Characterization of SCNP by NMR and SEC. Structure-property relationships related by pendent length and percent incorporation. Abstract: We present the synthesis of poly(oxanorbornene imide) single-chain nanoparticles (SCNP) by intrachain radical polymerization of pendant methacryloyl units. Well-defined poly(oxanorbornene imide)s were first prepared via ring-opening metathesis polymerization (ROMP) of methacryloyl-containing monomers. Handling and polymerizing these monomers requires some special care to prevent undesired premature reaction of the methacryloyl groups. Addition of AIBN to dilute solution of the ROMP polymers triggers intrachain radical polymerization of pendant methacryloyl groups, folding the linear polymers into SCNP. Characterization by NMR spectroscopy and SEC confirmed SCNP formation and revealed structure/property relationships related to methacryloyl pendent length and percent incorporation.